2018
DOI: 10.1111/cdev.13035
|View full text |Cite
|
Sign up to set email alerts
|

Examining Character Structure and Function Across Childhood and Adolescence

Abstract: Character strengths are an integral component of positive youth development that can promote flourishing. Developmental principles posit constructs become increasingly complex with age, yet this process has not been examined with character. Using a socioeconomically and ethnically diverse sample of 2,467 youth ages 9-19, bifactor models were estimated across elementary, middle, and high school-age groups to examine age differences in character structure and function. With successive age, a greater number of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 46 publications
(89 reference statements)
0
18
0
2
Order By: Relevance
“…Parent reports (Park & Peterson, 2006b;Shoshani, 2019) for pre-school children and self-reports for school children (Shoshani & Shwartz, 2018) could be used to evaluate the early development of character strengths and its moderators (e.g., school type or membership in a youth association; Ruch & Wagner, 2013). Furthermore, a recent study supported the notion that the structure of character strengths (which partially overlapped with the strengths in the VIA classification) becomes more differentiated and complex from late childhood to adolescence (Shubert, Wray-Lake, Syvertsen, & Metzger, 2019).…”
Section: Limitations and Future Directions For Research And Applicationsmentioning
confidence: 65%
“…Parent reports (Park & Peterson, 2006b;Shoshani, 2019) for pre-school children and self-reports for school children (Shoshani & Shwartz, 2018) could be used to evaluate the early development of character strengths and its moderators (e.g., school type or membership in a youth association; Ruch & Wagner, 2013). Furthermore, a recent study supported the notion that the structure of character strengths (which partially overlapped with the strengths in the VIA classification) becomes more differentiated and complex from late childhood to adolescence (Shubert, Wray-Lake, Syvertsen, & Metzger, 2019).…”
Section: Limitations and Future Directions For Research And Applicationsmentioning
confidence: 65%
“…Werner ( 1957 ) orthogenetic principle suggests that as development occurs, there is a process from a state of globality and lack of differentiation to a state of increasing differentiation, articulation, and integration. Returning again to the example of character, researchers have found that global character becomes more differentiated and specific as children become adolescents (Shubert et al, 2019 ). Mindset may follow a similar trajectory, the domains becoming more differentiated with age before later integration.…”
Section: Discussionmentioning
confidence: 99%
“…Mengenalkan karakter kebangsaan pada anak perlu didukung berbagai sumber dan desain pembelajaran yang sesuai dengan karakteristik anak. Namun, kenyataannya tantangan implementasi pendidikan karakter dalam proses pembelajaran merupakan akibat kurangnya pemahaman guru mengenai nilai karakter yang diajarkan, keterbatasan desain pembelajaran dan pemilihan pendekatan yang sesuai (Shubert et al, 2019). Perlu adanya program karakter yang terencana dan komprehensif merupakan langkah awal dan upaya terus menerus agar suatu nilai karakter dapat terintegrasi dengan semua aspek kehidupan sekolah (Lickona et al, 2011).…”
Section: Pendahuluanunclassified